2009
DOI: 10.1128/jb.00356-09
|View full text |Cite
|
Sign up to set email alerts
|

The Electron Transfer System of Syntrophically Grown Desulfovibrio vulgaris

Abstract: Interspecies hydrogen transfer between organisms producing and consuming hydrogen promotes the decomposition of organic matter in most anoxic environments. Although syntrophic coupling between hydrogen producers and consumers is a major feature of the carbon cycle, mechanisms for energy recovery at the extremely low free energies of reactions typical of these anaerobic communities have not been established. In this study, comparative transcriptional analysis of a model sulfate-reducing microbe, Desulfovibrio v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
183
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(199 citation statements)
references
References 51 publications
8
183
3
Order By: Relevance
“…This syntrophy occurs at trace sulfate concentrations. This approach of defined syntrophic growth enabled direct experimental measurement of the specific effects of associated bacteria on the growth, activity and gene expression of Dehalococcoides, similar to the approach taken for the study of Syntrophomonas wolfei with Methanospirillum hungatei (Beaty and McInerney, 1989), for the study of D. vulgaris with methanogens (Bryant et al, 1977;Scholten et al, 2007;Stolyar et al, 2007;Walker et al, 2009) and for the study of Desulfovibrio sp. strain SULF1 and Desulfovibrio fructosivorans with a dehalorespiring bacterium Desulfitobacterium frappieri TCE1 (Drzyzga et al, 2001;Drzyzga and Gottschal, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This syntrophy occurs at trace sulfate concentrations. This approach of defined syntrophic growth enabled direct experimental measurement of the specific effects of associated bacteria on the growth, activity and gene expression of Dehalococcoides, similar to the approach taken for the study of Syntrophomonas wolfei with Methanospirillum hungatei (Beaty and McInerney, 1989), for the study of D. vulgaris with methanogens (Bryant et al, 1977;Scholten et al, 2007;Stolyar et al, 2007;Walker et al, 2009) and for the study of Desulfovibrio sp. strain SULF1 and Desulfovibrio fructosivorans with a dehalorespiring bacterium Desulfitobacterium frappieri TCE1 (Drzyzga et al, 2001;Drzyzga and Gottschal, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of these genes suggests that the syntrophic growth of DE195 and DVH might have a different hydrogen transfer system than the DE195 isolate. Transcriptomic analysis of DVH syntrophically grown with a hydrogenotrophic methanogen compared with DVH grown in sulfate-limited monocultures showed that genes encoding hydrogenases Coo, Hyd and Hyn were among the most highly expressed and up-regulated genes (Walker et al, 2009). Therefore, differential regulation of genes encoding hydrogenases of DVH grown in DE195/ DVH compared with the DVH isolate should be further investigated, to elucidate the interspecies hydrogen transfer during syntrophic growth.…”
Section: Discussionmentioning
confidence: 99%
“…The specific community structure may depend on the hydrocarbon substrates, the available nutrients and/or specific biogeochemical characteristics. Genes encoding anaerobic hydrocarbon-degrading enzymes (for example, bssA, assA) have been detected in hydrocarbon-degrading methanogenic cultures (for example Aitken et al, 2013;Cheng et al, 2013;Fowler et al, 2012;Washer and Edwards, 2007) as well as genes involved in syntrophic processes such as H 2 and formate transfer, and flagella, amino-acid and coenzyme biosynthesis (Kato et al, 2009;Walker et al, 2009). Despite recent reports of hydrocarbon-degrading co-cultures of sulfate reducers and methanogens (Callaghan et al, 2012;Lyles et al, 2014), the diversity of key enzymes and genes involved in methanogenic hydrocarbon metabolism are not yet well described.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the syntrophic growth of sulfate-reducing bacteria (SRB) acting like secondary fermenters and methanogenic archaea [9][10][11] . Most recently, the metabolic interaction between Clostridia, acting as primary fermenters, and methanogenic archaea has also been studied 12,13 , highlighting a symbiotic process of interspecies hydrogen transfer that does not require physical interaction.…”
mentioning
confidence: 99%